Традиции Ильи Ильфа и Евгения Петрова и Компромисс Сергея Довлатова - Зайцева, Светлана (Studia Rossica Posnaniensia, 2020)
The aim of the study is to investigate common motifs, characters, metaphors and plots in Sergey Dovlatov’s Compromise and Ilya Ilf and Yevgeny Petrov’s novels The Twelve Chairs and The Little Golden Calf using the structural and comparative-historical methods. In this case study Compromise is treated as the text, in which Dovlatov determines the underlying principle for reading the short stories contained in his Compromise collection in the context of the novels The Twelve Chairs and The Little Golden Calf by Ilf and Petrov. The results of the research are confirmed by the contextual study of Dovlatov’s correspondence. This allows us to state that the novels of Ilf and Petrov are the subtext of Sergei Dovlatov’s work. The article opens totally new and inspiring directions of Dovlatov studies, since no other scholars have ever turned their attention to the relationships between Dovlatov’s works and the traditions of Ilf and Petrov.